Diversity, Oppression, and Social Functioning: Person-in-Environment Assessment and Intervention - Appleby, George A. (Pearson/Allyn and Bacon, 2007)
Keywords: Social work with minorities; Person-in-environment system; dept.swk; faculty_collection

Posttraumatic play: Towards acceptance and resolution - Dripchak, Valerie L. (Clinical Social Work Journal, 2007)
Many children who experience trauma demonstrate it through posttraumatic play (PTP). This type of play is seen by professionals as a repetitive reenactment of the traumatic event within the child's play. Reliving the event in this way may serve to retraumatize the child and lead to other psychiatric or behavioral problems. This article examines the issues surrounding childhood trauma and PTP. It uses a case study to illustrate the phases of a play therapy approach that incorporates Ericksonian principles, in order for the child to achieve resolution and acceptance. The countertransference issues that a clinician may encounter also are discussed.
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/049-629-250-370-634 tex.unique-id: [object Object]
Keywords: Play therapy; Posttraumatic play; Retraumatize; Trauma in children; dept.swk

Lesbian mothers with planned families: A comparative study of internalized homophobia and social support - DeMino, Kathleen A.; Appleby, George; Fisk, Deborah (American Journal of Orthopsychiatry, 2007)
This study compared the perception of social support and the degree of internalized homophobia for two demographically similar groups: lesbians with planned families and lesbians who did not have children. Results found that lesbians with planned families perceived significantly less social support from friends overall, from gay men and lesbian friends specifically, and more support from their families-of-origin than lesbians who did not have children. Lesbians with planned families also reported significantly higher internalized homophobia specific to disclosure of sexual identification. The authors suggest that selective disclosure may be an adaptive response rather than a true measure of internalized homophobia.
22 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/091-948-881-682-440 tex.unique-id: [object Object]
Keywords: Adult; Attitude; Child; Family Planning Services; Female; Homosexuality; Female; Humans; Internalized homophobia; Lesbian mothers; Maternal Behavior; Mothers; Percerption of social support; Planned families; Questionnaires; Self Concept; Social Support; adult; article; controlled study; demography; dept.swk; family; female; gender identity; homophobia; human; lesbian; male homosexual; social support

Diagnosing conduct problems of children and adolescents in residential treatment - Cameron, Mark; Guterman, Neil B (Child Care Quarterly, 2007)
This naturalistic study of diagnostic practice in residential treatment agencies for children investigated the use of the DSM-IVconduct disorder diagnosis and its association with residents' externalizing behaviors. The conduct disorder (CD) diagnosis was a poor predictor of participants' externalizing behaviors during their first few months in residence. Additionally, the assignment of the diagnosis was associated with the gender and race of study participants. Decisions of admissions personnel and practitioners in residential treatment facilities regarding their externalizing clients may not be well-served by use of DSM diagnoses. Assessments of caregivers may prove a useful adjunct to DSM diagnoses. © 2007 Springer Science+Business Media, LLC.
22 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-610-397-897-543 tex.type: [object Object]
Keywords: Adolescents; Children; Conduct disorder; DSM-IV validity; Diagnosis; Residential treatment; dept.swk

Patterns of interaction: Conceptualizing the crossroads between social structures, interpersonal actions, and psychological well-being - Keenan, Elizabeth King (Smith College Studies in Social Work, 2007)
Patterns of interaction theory directs social workers' attention to the relations between structures (psychological and social), and actions: the crossroads of continuity and change. Because it describes sequences of action by key participants that generate specific options at various points in a sequence, it serves as both theory and method for understanding and intervening with human beings and social structures. The use of patterns of interaction as an overarching construct illuminates the reciprocal relationships between social structures, interpersonal actions, and psychological well-being. This paper outlines a preliminary conceptualization of patterns of interaction theory and the methodology that grows out of it. The social service programs of Temporary Assistance to Needy Families (TANF) and a community-based case management welfare-to-work program illustrate how an ethical lens applied to patterns of interaction can help social workers intervene within complex relations to facilitate client growth. Patterns of interaction theory is a potentially effective way of describing and analyzing the therapeutic effects of a range of different social service programs.
tex.unique-id: ISI:000245064200005
Keywords: dept.swk; ⚠️ Invalid DOI